Transformation de l’espace et privatisation des ressources communautaires au Pérou - María Luisa Burneo (Cahiers des Amériques Latines)
This paper analyzes the relationship between the Peruvian state and indigenous peasant communities through a long history of recognition, protectionism and dispossession. It focuses on the changes produced by the neoliberal reforms of the nineties and the subsequent economic liberalization of the communal land market that resulted on private investments. By studying different cases of peasant communities from ‘Bosque Seco’ in the Peruvian north coast, we show how the convergence of state action, private enterprises and the response of communal governments not only has transformed the social space by changing property and control regulations, but also how the space has been reshaped as an inhabited place, product of an historical process that gives sense and legitimates the communal institution.